The legacy of the Ottoman library in the libraries of the Turkish Republic - İCİMSOY, AHMET OĞUZ (WALTER DE GRUYTER GMBH, 2008)
With the proclamation of the Turkish Republic in 1923 not only was the Ottoman Empire but also many of its institutions abolished. Many of the classical Ottoman institutions had ceased to operate effectively and had become increasingly irrelevant to the needs of society. In the early Republican period many of these institutions including law, education, the alphabet - both the written and the spoken language, music etc., were replaced wholesale by European models, but in some cases we see that Ottoman attitudes and practices infiltrated into the new order. Particularly in education was it more difficult to change attitudes, so that while a European-styled system of education was established, there was a failure to provide it with a comprehensive library system to support it. Today in Turkey the concept of a general library operating for the general public and for research is yet to be adopted. This article attempts to examine the attitudes and practices that have held fast in the library system today as part of our heritage from the last century of the Ottoman Empire. It concludes that the professional work of the modem Turkish librarian and the development of Turkish schools for training librarians are contributing to a change in perception.
Keywords: CONSORTIUM; TURKEY